Role of Thinking in Learning - Kadel, Purna Bahadur (Journal of NELTA Surkhet, 2015)
Thinking is essential for learning. Thinking is inextricably intertwined with learning. Teaching thinking refers to teaching critical and creative thinking skills and problem solving tasks. Critical thinking incorporates reasoning, logical judgment, metacognition, reflection, and mental process in course of learning. It involves evaluation, analyzing, and interpreting the problems to find out the solution. Creative thinking can be enhanced through multiple intelligence, affective factors, and innovative curriculum. Metacognition and thinking are must to solve any task in learning language. Journal of NELTA Surkhet Vol.4 2014: 57-63